2002
DOI: 10.3758/cabn.2.4.341
|View full text |Cite
|
Sign up to set email alerts
|

Somatic markers, working memory, and decision making

Abstract: The somatic marker hypothesis formulated by Damasio (e.g., 1994;Damasio, Tranel, & Damasio, 1991) argues that affective reactions ordinarily guide and simplify decision making. Although originally intended to explain decision-making deficits in people with specific frontal lobe damage, the hypothesis also applies to decision-making problems in populations without brain injury. Subsequently, the gambling task was developed by Bechara (Bechara, Damasio, Damasio, & Anderson, 1994) as a diagnostic test of decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
166
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(186 citation statements)
references
References 46 publications
16
166
2
2
Order By: Relevance
“…We demonstrate a similar finding involving emotional, rather than nonemotional stimuli, thus further extending the generalizability of IQ. Furthermore, our results complement findings 22 from other types of tasks showing that intelligence (and working memory) are very important for performance involving pre-anticipatory emotional activation (Bechara, Damasio, Tranel, & Anderson, 1998;Hinson, Jameson, Whitney, 2002) and that EI measured as a trait fails to predict performance in this domain (Demaree, Burns, & DeDonno, 2010).…”
Section: Discussionsupporting
confidence: 35%
“…We demonstrate a similar finding involving emotional, rather than nonemotional stimuli, thus further extending the generalizability of IQ. Furthermore, our results complement findings 22 from other types of tasks showing that intelligence (and working memory) are very important for performance involving pre-anticipatory emotional activation (Bechara, Damasio, Tranel, & Anderson, 1998;Hinson, Jameson, Whitney, 2002) and that EI measured as a trait fails to predict performance in this domain (Demaree, Burns, & DeDonno, 2010).…”
Section: Discussionsupporting
confidence: 35%
“…Thus, by interfering with WM function, we prevented the development of the affective reactions that appear to guide good GT decision making. The data obtained by Hinson et al (2002) demonstrated that performance on the GT and formation of a somatic marker are dependent on WM. However, WM is a multicomponent system (e.g., Baddeley, Chincotta, & Adlam, 2001), and more data are needed to specify what aspects of WM are involved in the GT.…”
mentioning
confidence: 93%
“…Two consistent findings in ADHD research have been poor sustained attention [4][5][6] and attenuated electrodermal activity (EDA) [7][8][9]. The importance of EDA as a "somatic marker" for the consequences of different behaviours [10] has been well established in decision-making tasks however it is not clear how somatic markers are related to other executive functions such as, for example, sustained attention [11]. In the present study we investigate whether the attenuated task-related EDA of children with ADHD might contribute to their poor performance on sustained attention tasks.…”
Section: Introductionmentioning
confidence: 99%